THE EFFECT OF VARIOUS NITROGEN FERTILIZER DOSAGE ON GROWTH AND YIELD OF Mentha piperita Linn. ON ALUVIAL SOIL - Dwi Nirwanto; Siti Hadijah; Rahmidiyani . (Jurnal Sains Pertanian Equator, 2020)
Mentha piperita Linn is one of the annual herbaceous plants that has many benefits, such as mint oil which is used as an aroma and flavor enhancer in food and drinks, medicine, perfume, cosmetics, and other refreshing products. Efforts to increase mint plant production by expanding cultivation land on alluvial soils must be balanced with intensification efforts, such as applying nitrogen fertilizer because mint is a leaf-producing plant that requires a lot of N elements. This study aims to determine the best dose of nitrogen fertilizer in increasing growth and yield of mint on alluvial soils. This research was conducted from October 21, 2019 to January 24, 2020. The method used was a Completely Randomized Design. The treatments consisted of 5 levels namely n1 = 0.09 g N/polybag, n2 = 0.18 g N/polybag, n3 = 0.28 g N/polybag, n4 = 0.37 g N/polybag, n5 = 0.46 g N/polybag. All treatments were repeated 5 times, each treatment consists of 4 plant samples. The results showed that the best dose of nitrogen fertilizer for increasing Mentha piperita Linn. production was 0.46 g N/polybag on variable leaf weight per plant. Keywords: Alluvial Soil, Mentha piperita Linn, Nitrogen Fertilizer